Empowering farmers A comprehensive guide to KVK Portal of ICAR - Gautam, U S; Burman, R R; Jha, Sujeet K; Arora, Alka; Marwaha, Sudeep; Pal, Soumen; Choudhary, Naseeb (Indian Farming, 2024)
This article delves into the transformative role of Krishi Vigyan Kendras (KVKs), operating under the aegis of Indian Council of Agricultural Research (ICAR), in elevating the socio-economic status of farmers across India. As integral component of the National Agricultural Research System (NARS), KVKs serve as dynamic knowledge and resource centres, focused on the assessment, refinement, and dissemination of location-specific agricultural technologies. The Krishi Vigyan Kendra (KVK) portal, developed by the ICAR, designed to provide farmers with a plethora of resources and services stands out as a beacon of innovation. Through on-farm demonstrations, technology assessments, and capacity-building programme, KVKs facilitate to empower farmers with the latest advancements in agriculture. The collaborative efforts of KVKs with public, private, and voluntary sectors underscore their comprehensive approach to improve the agricultural economy at the district level. The current arcticle explores the multifaceted functions of KVKs, emphasizing their pivotal role in connecting research initiatives with the extension system and farmers. Moreover, this arcticle serves as a comprehensive exploration of how KVKs, as catalysts for agricultural innovation, contribute to the holistic betterment of farmers and the sustainable development of Indian agriculture.